Eastern Late roman fine ware imports in Bracara Augusta (Braga, Portugal) - Carlos Quaresma, José; Morais, Rui (Rei Cretariae Romanae Fautorum Acta, 2012)
The excavations carried out in the past 30 years under Projecto de Salvamento de Bracara Augusta (Project for the Rescue of Bracara Augusta) have enabled us to determine the importations and the economy trends of this Roman city situated in the western periphery of the empire. if studies of early empire imports have been privileged, little is known about the Late period when the city was the capital of all Gallaecia. the only articles about late imported goods were published in LRCW 1, where a brief analysis of the fine ware production was presented in the context of the African and Late eastern amphorae, and in the course of a former RCRF congress exclusively dedicated to Late Hispanic terra sigillata.